2022
DOI: 10.32670/fairvalue.v4i9.1589
|View full text |Cite
|
Sign up to set email alerts
|

Analisis pengaruh organizational resilience, job satisfaction, organizational learning culture, dan turnover intention terhadap business performance pada perusahaan pertamina

Abstract: This study aimed to analyze the influence of Organizational Resilience, Job Satisfaction, Organizational Learning Culture, and Turnover Intention on Business Performance. Business Performance. The data analysis technique in this study used several statistical tests to apply structural equation modeling (SEM) as a tool. The sample data collection method in this study used purposive sampling with a sample of employees of PT. Pertamina. This study used a questionnaire distributed online. The sample from the popul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…This study has successfully demonstrated organizational resilience's positive and significant influence on company performance in publicly listed hospitals in Indonesia. This finding informs those hospitals possessing organizational resilience, capable of enduring fierce competition and constraints, and transforming challenges into organizational learning, can effectively enhance company performance [46][47][48]50] . However, this situation does not align with the findings of Comfort et al (2001), who asserted that organizational performance often diminishes in increasingly complex environments [45] .…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…This study has successfully demonstrated organizational resilience's positive and significant influence on company performance in publicly listed hospitals in Indonesia. This finding informs those hospitals possessing organizational resilience, capable of enduring fierce competition and constraints, and transforming challenges into organizational learning, can effectively enhance company performance [46][47][48]50] . However, this situation does not align with the findings of Comfort et al (2001), who asserted that organizational performance often diminishes in increasingly complex environments [45] .…”
Section: Discussionmentioning
confidence: 73%
“…Beuren et al (2021) found that organizational resilience positively impacts business performance and job satisfaction [48] . Similarly, Fathi et al (2021) and Suciariani et al (2022) ascertained that organizational resilience has a significant positive influence on firm performance [49,50] . Fathi et al (2021) study revealed that competitive advantage partially mediates the relationship between organizational resilience and firm performance [49] .…”
Section: Theorical Framework and Hypothesismentioning
confidence: 99%